Safety and efficacy of l‐valine produced using Corynebacterium glutamicum CGMCC 11675 for all animal species. (4th March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The product subject of this assessment is l ‐valine produced by fermentation with a strain of Corynebacterium glutamicum (CGMCC 11675). It is intended to be used in feed and water for drinking for all animal species and categories. Owing to the uncertainties regarding the possible genetic modification of the original production strain, the FEEDAP Panel cannot conclude on the safety of the additive l ‐valine produced with C . glutamicum CGMCC 11675 for the target species, the consumers, the users and the environment. The FEEDAP Panel has concerns on the safety for the target animals of the simultaneous oral administration of valine‐containing additives via feed and water for drinking. In the absence of data, the FEEDAP Panel cannot conclude on the potential of l ‐valine produced with C. glutamicum CGMCC 11675 to be toxic by inhalation, irritant to skin or eyes, or on its potential to be a dermal sensitiser. The product is considered an efficacious source of the amino acid l ‐valine for all animal species. The supplemental l ‐valine requires protection against rumen degradations in order to be as efficacious in ruminant as in non‐ruminant species.